New insights into bacterial mechanisms and potential intestinal epithelial cell therapeutic targets of inflammatory bowel disease - Liang, Bing; Wu, Changhao; Wang, Chao; Sun, Wenshe; Chen, Wujun; Hu, Xiaokun; Liu, Ning; Xing, Dongming (Frontiers in Microbiology, 2022)
The global incidence of inflammatory bowel disease (IBD) has increased rapidly in recent years, but its exact etiology remains unclear. In the past decade, IBD has been reported to be associated with dysbiosis of gut microbiota. Although not yet proven to be a cause or consequence of IBD, the common hypothesis is that at least some alterations in the microbiome are protective or pathogenic. Furthermore, the development of biologics targeting cytokines and receptors involved in the pathogenesis of IBD has led to better therapeutic outcomes and improved disease progression. However, about one-third of patients still do not respond, or their response decreases over time. This article presents a selective overview of recent studies of pathophysiological mechanisms of IBD in biological models. In particular, we review the bacterial species, certain fungal and viral members, and their related functional pathways potentially protective and promotive of IBD. Lastly, we present the recent emergence of potential IBD therapeutic targets, including crucial modulators and signaling pathways in intestinal epithelial cells, endothelial cells, and immune cells, aiming to provide additional insights to improve this increasingly common disease.